Workplace spirituality: Making a difference - Yochanan Altman; Judi Neal; Wolfgang Mayrhofer (De Gruyter, 2022)
A state-of-the-art overview of the field of management, spirituality and religion, comprising concise chapters written by experts in the sub-fields and edited by recognized leaders in the field of management, spirituality and religion.
Keywords: 650; Management; religion; spirituality; working lives; organizations